Analisa Dan Perancangan Sistem Informasi PPDB Online Berbasis Website Menggunakan Metode Waterfall Di SMK Gema Bangsa - Haqun Baitika; Yayah Zakiyah; Alfi Ardhiansyah; Saprudin (CV. Shofanah Media Berkah, 2023)
Based on the analysis carried out, the manual admissions system at Gema Bangsa Vocational School experiences several obstacles including frequent human errors in the calculation process, writing and recording student names on student admission reports, requiring a long time in searching for data, delays in information and storage of evidence of student acceptance that is less effective. From the various kinds of problems above, the author made a study entitled